ViMoIS: The Student Violation Point Monitoring Information System - Ahmad Fachrur Rozy; Rangsang Purnama (Universitas Hamzanwadi, 2022)
Although the rules have been enforced, children's behavior in schools often cannot be monitored by parents even when children commit violations. This is because the school has not implemented information system technology for parents to track violations committed by their children in the school. The purpose of this study is to build a violation point information system (ViMoIS) for students so that their recording can be done digitally and can be monitored by parents. The location of study was conducted in one of the High Schools in Gresik. The data collection technique uses the Focus Group Discussion (FGD) method. The model used to build this system is waterfall starting with three stages of that is, analysis, design, and testing. The results of the study were in the form of a Web-Based Student Violation Point Monitoring Information System (ViMoIS). Based on the results of black box testing that all components in this system run smoothly (success). The existence of a ViMoIS is expected to modernize the process of recording student budgeting so that old people can monitor their children's behavior in schools.